2018
DOI: 10.3382/ps/pex368
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the performance of Hy-Line Brown laying hens fed soybean or soybean-free diets using cage or free-range rearing systems

Abstract: This study evaluated egg production and quality variables of caged and free-range Hy-Line Brown laying hens fed soybean meal (SBM) and soybean-meal-free (SBMF) diets. Hens were randomly assigned to the same 2 dietary treatments within 3 location blocks. SBM and SBMF diets with equivalent calculated nutrient content were prepared based on Hy-Line Brown rearing guidelines. The SBMF diets utilized cottonseed meal, corn distillers dried grains with solubles, corn gluten meal, and wheat middlings in place of dehull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…The most widely and commonly used rearing systems are free‐range (FRS) and conventional cage‐rearing systems (CRS), and the chickens are raised under CRS conditions tending to show superior feed efficiency and growth performance (Wang et al., ). Similar findings had been reported for different poultry breeds, including broiler chickens (Li et al., ), laying hens (Al‐Ajeeli et al., ), and local ducks (Zhang et al., ). Moreover, compared with other rearing systems, the CRS is an effective approach for maximizing the utilization of space and stocking density, and decreasing administrative costs and exposure to contaminants.…”
Section: Introductionsupporting
confidence: 85%
“…The most widely and commonly used rearing systems are free‐range (FRS) and conventional cage‐rearing systems (CRS), and the chickens are raised under CRS conditions tending to show superior feed efficiency and growth performance (Wang et al., ). Similar findings had been reported for different poultry breeds, including broiler chickens (Li et al., ), laying hens (Al‐Ajeeli et al., ), and local ducks (Zhang et al., ). Moreover, compared with other rearing systems, the CRS is an effective approach for maximizing the utilization of space and stocking density, and decreasing administrative costs and exposure to contaminants.…”
Section: Introductionsupporting
confidence: 85%
“…In the U.S., most poultry diets utilize the lowest cost ingredients, typically corn and soy as the sources of energy and protein, respectively, to keep the cost of nutrition low [24]. While soybean meal (SBM) represents over 40% of the poultry diet [25], concerns about the anti-nutritive properties of SBM [26,27], the high concentration of isoflavones on bird or human health [28], have necessitated the search for alternative feed sources that may reduce or replace SBM in poultry diets. Climate change and increased demands from fisheries production are also expected to increase costs [29,30].…”
Section: Role Of Dietary Protein Sourcementioning
confidence: 99%
“…All laying hens in this experiment were a subset of hens used in the study reported by Al-Ajeeli et al (IACUC 2017-0072) [25]. Briefly, the study started with 246 11-week old Hy-Line Brown pullets, divided into either the caged or cage-free group at 20 weeks of age (120 for caged, and 126 for cage-free).…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 120 layers at 63 weeks were used in this study. These older hens were used for this study as the birds were part of the performance study reported in [21], and could not be euthanized at an earlier point. Hens were distributed in wire cages a 50.8 cm W × 30.5 cm L × 30.5 cm H per cage (1549 cm 2 /hen) with one nipple drinker for every two cages in a randomized block design.…”
Section: Live Animal Studymentioning
confidence: 99%